Mos induces the in vitro activation of mitogen-activated protein kinases in lysates of frog oocytes and mammalian somatic cells. - Shibuya, E K (1993)
Mitogen-activated protein kinases (MAPKs) are rapidly and transiently activated when both quiescent Go-arrested cells and G2-arrested oocytes are stimulated to reenter the cell cycle. We previously developed a cell-free system from lysates of quiescent Xenopus oocytes that responds to oncogenic H-ras protein by activating a MAPK, p42MAPK. Here, we show that the oncogenic protein kinase mos is also a potent activator of p42MAPK in these lysates. Mos also induces p42MAPK activation in lysates of activated eggs taken at a time when neither mos nor p42MAPK is normally active, showing that the mos-responsive MAPK activation pathway persists beyond the stage where mos normally functions. Similarly, lysates of somatic cells (rabbit reticulocytes) also retain a mos-inducible MAPK activation pathway. The mos-induced activation of MAPKs in all three lysates leads to phosphorylation of the pp90rsk proteins, downstream targets of the MAPK signaling pathway in vivo. The in vitro activation of MAPKs by mos in cell-free systems derived from oocytes and somatic cells suggests that mos contributes to oncogenic transformation by inappropriately inducing the activation of MAPKs.